2012
DOI: 10.1029/2011ja017452
|View full text |Cite
|
Sign up to set email alerts
|

Global response of the ionosphere to atmospheric tides forced from below: Comparison between COSMIC measurements and simulations by atmosphere‐ionosphere coupled model GAIA

Abstract: This paper for the first time presents a detailed comparison between simulated and observed global electron density responses to different atmospheric tides forced from below. The recently developed Earth's whole atmospheric model from the troposphere to the ionosphere, called GAIA, has been used for the simulation of the electron density tidal responses. They have been compared with the extracted from the COSMIC electron density data tidal responses for the period of time October 2007 to March 2009. Particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 69 publications
(93 reference statements)
2
49
0
2
Order By: Relevance
“…Hagan et al (2009) reported the existence of stationary planetary wave-4 (SPW4) oscillation in the upper mesosphere and lower thermosphere (MLT) region, caused by the nonlinear interaction between DE3 and the migrating tide DW1. Since then, the importance of stationary planetary waves, SPW4/SPW3, contributing to the longitudinal WN4/WN3 patterns in the upper atmosphere, has also been supported by both model simulations (e.g., Oberheide et al, 2011a;Pancheva et al, 2012) and in situ observations (e.g., Kil et al, 2010;Lühr and Manoj, 2013;Xiong and Lühr, 2013;Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Hagan et al (2009) reported the existence of stationary planetary wave-4 (SPW4) oscillation in the upper mesosphere and lower thermosphere (MLT) region, caused by the nonlinear interaction between DE3 and the migrating tide DW1. Since then, the importance of stationary planetary waves, SPW4/SPW3, contributing to the longitudinal WN4/WN3 patterns in the upper atmosphere, has also been supported by both model simulations (e.g., Oberheide et al, 2011a;Pancheva et al, 2012) and in situ observations (e.g., Kil et al, 2010;Lühr and Manoj, 2013;Xiong and Lühr, 2013;Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 86%
“…It should be noted that the sampling time step of CHAMP data is also 10 s and the response function for CHAMP is the same as for GOCE. Following Park et al (2014), to avoid effects caused by equatorial plasma bubbles (e.g., Illés-Almár et al, 1998;Park et al, 2010) and to avoid artificial fluctuations due to the combination of low background level and CHAMP density accuracy (Liu et al, 2005), we consider only CHAMP data between 09:00 and 18:00 LT. Also, observations during disturbed periods (Kp > 4.0) are not considered.…”
Section: Gravity Waves Observed By Champmentioning
confidence: 99%
“…The combined amplitudes of these two resulting components can be comparable with that of the DE3 (Oberheide et al, 2011). Furthermore, based on observations from the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellites and on simulations with the Ground-to-topside model of Atmosphere and Ionosphere for Aeronomy (GAIA), Pancheva and Mukhtarov (2011), Pancheva et al (2012) showed the important contribution of the stationary planetary waves, SWP4/SWP3, to the WN4/WN3 ionospheric structures as well as the dependence of the WN4/WN3 hemisphere asymmetry on the SE2/SE1 tides.…”
Section: Introductionmentioning
confidence: 99%